INVESTIGATION OF THE MISCONCEPTION IN NEWTON II LAW - Yudi Kurniawan (JURNAL PENA SAINS, 2018)
This study aims to provide a comprehensive description of the level of the number of students who have misconceptions about Newton's II Law. This research is located at one State Junior High School in Kab. Pandeglang. The purposive sampling was considering used in this study because it is important to distinguish students who do not know the concept of students who experience misconception. Data were collected using a three tier-test diagnostic test and analyzed descriptively quantitatively. The results showed that the level of misconception was in the two categories of high and medium levels. It needs an innovative teaching technique for subsequent research to treat Newton's Newton misconception.